For the record [large type] - Jennings, Regina (Regina Lea) (Thorndike Press, 2017)
Betsy Huckabee might be a small-town girl, but she has big-city dreams. Writing for her uncle's newspaper will never lead to independence, and the bigger newspapers don't seem interested in the Hart County news. Trying a new approach, Betsy pens a romanticized serial for the ladies' pages, and the new deputy provides the perfect inspiration for her submissions. She'd be horrified if he read her breathless descriptions of him, but these articles are for a newspaper far away. No one in Pine Gap will ever know. Deputy Joel Puckett didn't want to leave Texas, but this job in tiny Pine Gap is his only shot at keeping his badge. With masked marauders riding every night, his skills and patience are tested, but even more challenging is the sassy journalist lady chasing him.